JOURNEY OF A WORKING MOM AND HER SON WITH DOWN SYNDROME - Shahzad, Saadia (Journal of Ayub Medical College Abbottabad, 2015)
Trisomy 21, chromosomal disorder related with Down syndrome (DS), is the most common cause leading to learning disability among all races and all human population. Having a child with Down syndrome in developed world has now become less of an unfortunate incidence in the lives of the parents; not because they do not realize the tough road ahead for their child as compared to other siblings but due to the fact that they have got a comprehensive and cohesive support system running for these children at every stage of life that builds up the child to his/her full potential. The present special communication is about personal experience of a working mother with her son with Down syndrome. Keywords: Down syndrome, Experience, Mother